Estrutura da CLC em Áreas de Floresta e Pastagem na Amazônia usando Simulação de Grandes Vórtices - Avelar, James; Fisch, Gilberto; Rizza, Umberto (Ciência e Natura, 2007)
Some characteristics of the development of Convective BoundaryLayer (CBL) were studied for forest and pasture areas in Amazonia,using a large eddy simulation (LES) model. Observational data wereused for the initialization. The CBL was well simulated for both areas,with errors for its height above the pasture and above the forest of 1%and 5%, respectively.